“Selam bundle”: thrift shopping as Malaysian social class integration platform - Chan, Rachel Suet Kay (Penerbit Universiti Kebangsaan Malaysia, 2020)
The mainstream rise of “bundle” clothing consumption in Malaysia mirrors the global trend of thrift shopping. Theories about this phenomenon range from the birth of recessionistas, to environmental conservation and identity construction. In this paper, I examine the trend of “selam bundle”, or diving into clothingbundles in thrift shops, where people deliberately purchase material goods to communicate their fashion tastes to the public. Bourdieu’s concepts of habitus and field are also used to elucidate this phenomenon. I theorise that the act of thrift shopping, or “selam bundle” here is not caused entirely due to a lack of funds based on social class, as individuals from various levels of income participate in this activity. Instead, I view “selam bundle” as an act of increasing one’s “street cred” or social capital, where the more unique the find, the more “street cred” one achieves. This is also an activity that is common among the hipster subculture. Observations about thrift shopping or “selam bundle” were made using a mixed-method approach, combining visits to thrift stores, watching YouTube videos of thrift bloggers, reading their blogs, obtaining newspaper interviews and feature stories about thrift shoppers and thrift shops, and obtaining data from social media, as well as data from a large-scale survey titled Platform Integrasi:Pendekatan ‘Top-Down’ dan ‘Bottom-Up’ Dalam Mendepani Cabaran Kesepaduan Sosial (Integration Platforms: ‘Top-Down’ and ‘Bottom-Up’ Approaches to Facing Challenges in Social Cohesion). As this is a shopping act that transcends the usual social categories of social class, I theorise that “selam bundle” can be seen as a potential platform of social integration, driven by the grassroots or everyday-defined approach to constructing identity.